Three-dimensional hepatocyte culture system for the study of Echinococcus multilocularis larval development. - Li Li; Bing Chen; Hongbin Yan; Yannan Zhao; Zhongzi Lou; Jianqiu Li; Baoquan Fu; Xingquan Zhu; Donald P McManus; Jianwu Dai; Wanzhong Jia (Public Library of Science (PLoS), 2018)
Hepatocyte-based metacestode culture is an attractive method to study alveolar echinococcosis (AE), but it is limited by the relatively short lifespan of cultured hepatocytes in maintaining their normal function.We describe a three-dimensional (3D) hepatic culture system developed from co-cultured hepatocytes and mesenchymal stem cells using a collagen scaffold to study the development of Echinococcus multilocularis larvae. This 3D culture system preserved the function of hepatocytes for a longer period of time than their monolayer counterparts, with albumin secretion, 7-ethoxyresorufin O-deethylation activity, urea synthesis, CYP3A4 and CYP2D6 activity being highly preserved for 21-28 days. The expression levels of hepatocyte-specific genes including CLDN-3, Bsep, AFP, G6P, A1AT, CYP3A4 and NR1I3 were significantly higher in the 3D cultured system compared with their monolayer counterparts after 14-days in culture. Additionally, in the presence of 3D cultured hepatocytes, 81.2% of E. multilocularis protoscoleces rapidly de-differentiated into infective vesicles within eight weeks. Transcriptomic analyses revealed 807 differentially expressed genes between cultured vesicles and protoscoleces, including 119 genes uniquely expressed in protoscoleces, and 242 genes uniquely expressed in vesicles. These differentially expressed genes were mainly involved in parasite growth relating to the G-protein coupled receptor activity pathway, substrate-specific transmembrane transporter activity, cell-cell adhesion process, and potentially with neuroactive ligand-receptor interaction.This culture system provides a valuable advance in prolonging hepatocyte functionality, a foundation for future in-depth analysis of the host-parasite interaction in AE, and a useful model to evaluate potential therapeutic strategies to treat AE.